Phytoremediation Effectiveness Azolla sp. and Ipoemea Aquatica Towards Amonia Levels Reduction in Tilapia (Oreochromis niloticus) Water Cultivation - Aditya, Lisa Ayu; Latuconsina, Husain; Prasetyo, hamdani Dwi (Agrikan Jurnal Agribisnis Perikanan, 2023)
Tilapia is one type of freshwater fish that has a lot of demand in the market. Therefore, the production of tilapia aquaculture is increasing. Increased production of aquaculture causes a decrease in water quality due to the large number of metabolic wastes. Fish farmers usually require a large amount of money to overcome the decline in the quality of aquaculture pond water. For this reason, it is necessary to apply techniques to improve the quality of aquaculture pond water at an affordable cost. Azolla sp and Ipoemea aquatica are plants that can absorb environmental contaminants. The research method used was experimental method with untreated pool water samples (control), pool water samples treated with kale (Treatment 1), pool water samples treated with Azolla sp. (Treatment 2) and pond water samples with the combination treatment of kale and Azolla sp. (Treatment 3). Ammonia levels in Tilapia pond water samples were statistically analyzed using the SPSS application. The results showed that kale and Azolla sp. tends to be effective in reducing ammonia levels in Tilapia rearing pond water. The water spinach treatment had a higher value in reducing ammonia levels in the sample water of the tilapia rearing pond, which was 5.99 compared to the Azolla sp. of 3.22 and the combination treatment of 5.95.